تصميم الألعاب اللغوية لتنمية مهارة كلام المبتدئين باستخدام مفردات العربية بين يديك - Dina Fitrah Insani; Rizal Firdaus (Rayah Al-Islam, 2020)
Arabic is the language of the Koran and the Hadith, with this language we can understand both them. However, at this time many people assume that Arabic is difficult, especially in getting used to speak in this language. Therefore, it is appropriate for Arabic language teachers to create a pleasant way when teaching Arabic and make it easier to learn. The way of teaching is to use language games. T he researcher used the descriptive-analytical method based on the qualitative analysis model for Miles and Huberman, then followed the three steps of data limit and then presented and conclusion to obtain the important information in the analysis of language games to develop speech skill and design it using vocabulary bayna yadaik book. In this journal the researcher chose three language games aimed at improving the speaking ability of beginner-level students and designing this game using the vocabulary in the book Al-Arabiyyah Baina Yadaik The first volume from Chapters one through four because this vocabulary is appropriate for beginners. These Games are game Khomsu As'ilah, Nabroh Games and Ana Anta Games.